The characteristics of methane adsorption capacity and behavior of tectonic coal - Zhang, Hang; Zhang, Xiaobing; Zhang, Yugui; Wang, Zhenzhi (Frontiers in Earth Science, 2023)
The research of methane adsorption on tectonic coal is an important content to gas disaster prevention and coalbed methane (CBM) exploration in outburst coal seams. Many projects of methane adsorption capacity and behavior of tectonic coal, such as adsorption difference between tectonic coal and its untectonic coal, adsorption evaluation of tectonic coal, factors for adsorption capacity of tectonic coal, gas-solid coupling feature in tectonic coal and supercritical adsorption phenomena of tectonic coal, were carried out by scientists. Combined with a long-term study on organic matter structure and methane adsorption of tectonic coal, the author summarized recent-years’ researches on adsorption capacity and behavior of tectonic coal-methane at home and abroad from the dispute of adsorption ability determination, the thermodynamic characterization of methane adsorption capacity, and the methane adsorption behavior of quantum chemical calculation of the adsorption and the gas content calculation based on loss compensation, respectively. It is believed that the coal structure controls the methane adsorption capacity and behavior characteristics of different tectonic coals, and from the perspective of thermodynamics, the adsorption capacity of different types of coals can be better distinguished. In the future, a more scientific and complete quantum chemical calculation of methane adsorption by tectonic coal and a compensation method based on instantaneous emission loss should be established, so as to better reveal the methane adsorption behavior of tectonic coal and the mechanism of coal and gas outburst. The research has a reference to fine research of coal adsorption and CBM exploration practices.